Profit Estimation Model in Aquaculture Based on Market Preference: Application to Red Tilapia Culture in Reservoir of Wadaslintang, Indonesia - Dian Wijayanto; F.X. Sugianto; D. Poerwono (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
The purpose of this study was to develop the model of profit estimation in Aquaculture. This research used a model of von Bertalanffy length growth combined with the length-weight relationship, and developed an equation of time harvest to produce the target of fish weight as the market preferences. That also developed an equation to estimate the fish biomass, and the profit in aquaculture. The Profit is a total of revenue minus total of cost. Both the harvested biomass of fish and price of fish affect the revenue of aquaculture. The components of costs were a cost of seed procurement, cost of feed procurement, cost of transportation of products and the daily cost. The daily cost of aquaculture in floating cages were a cost of labour, cost of vitamins, cost of energy, cost of assets depreciation, cost of supporting equipment and cost of maintenance assets that converted to IDR (Indonesian Rupiah) (day) -1. The research proved if lthe model in this study could be used to estimate the profit of aquaculture. In case of red Tilapia culture (floating cage) in Reservoir of Wadaslintang, aquaculture at 120 days produced a fish average weight of 200 g (profit IDR. 13,507,167), then at 143 days produced 250 g (profit IDR. 17,975,723), at 164 days produced 300 g (profit IDR. 21,853,697), at 185 days produced 350 g (profit IDR. 25,387,418), at 204 days produced 400 g (profit IDR. 28,181,081), at 223 days produced 450 g (profit IDR. 30,507,200), and at 242 days produced 500 g (profit IDR. 32,297,418). Keywords: profit, von Bertalanffy, floating cage, Red Tilapia, Reservoir of Wadaslintang